Two precatalysts for application in asymmetric homogeneous hydrogenation. Issue 10 (4th September 2014) - Meißner, Antje; Pribbenow, Cornelia; Drexler, Hans‐Joachim; Heller, Detlef
<x xml:space="preserve">Abstract</x> The title compounds, [(1R, 1′R, 2R, 2′R)‐2, 2′‐bis(diphenylphosphanyl)‐1, 1′‐dicyclopentane](η4‐norbornadiene)rhodium(I) tetrafluoridoborate, [Rh(C34H36P2)(C7H8)]BF4, (I), and [(1R, 1′R, 2R, 2′R)‐2, 2′‐bis(diphenylphosphanyl)‐1, 1′‐dicyclopentane][η4‐(Z, Z)‐cycloocta‐1, 5‐diene]rhodium(I) tetrafluoridoborate dichloromethane monosolvate, [Rh(C34H36P2)(C8H12)]BF4·CH2Cl2, (II), are applied as precatalysts in asymmetric homogeneous hydrogenation, e.g. in the reduction of dehydroamino acids, affording excellent enantiomeric excesses [Zhu, Cao, Jiang & Zhang (1997). J. Am. Chem. Soc.119, 1799–1800].